2019
DOI: 10.23893/1307-2080.aps.05708
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and evaluation of the anti-cancer activity of silver nanoparticles by natural organic compounds extracted from cyperus sp. rhizomes

Abstract: The synthesis of metallic nanoparticles has become an important issue in recent decades due to their various beneficial and unique properties and biomedical and industrial applications 1. Nanotechnology is seeking to synthesize nanoparticles have substantial biomedical applications because of their unique characteristics and their green nature due to using some medicinal plants as ABSTRACT The object of this work is biosynthesizing AgNPs from extracts of Cyperus sp. galingale rhizomes, studying their character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…UV-Visible spectral analysis of the bio-synthesized AgNPs from pineapple juice and their color were checked in this test to confirm the formation of AgNPs (16) . The color change of the mixture solution from yellow to the brown color at peak 410 nm,and that agree with results of (6,7) .…”
Section: Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…UV-Visible spectral analysis of the bio-synthesized AgNPs from pineapple juice and their color were checked in this test to confirm the formation of AgNPs (16) . The color change of the mixture solution from yellow to the brown color at peak 410 nm,and that agree with results of (6,7) .…”
Section: Characterizationsupporting
confidence: 88%
“…The increasing of inhibition zone relates with the combination of the Ag nanopoarticle with antibiotics which increase methods of killing bacteria in vitro and that is called synergistic effect between AgNPs and antibiotics (24) . The role of silver nanoparticles biosynthesized from natural organic compounds in fruits extracts may be play an important agent against microbes (7) . referred to that silver nanoparticle which produced in the green chemistry method is considered potential nano-drug against human microbes' pathogens in vitro.…”
Section: Figure 1 Edx Images Of Agnpmentioning
confidence: 99%
See 1 more Smart Citation
“…Where it showed that the percentage of live cells of the cancerous bio-line MDA cells at (32.89-71.51) %, while the percentage of the normal healthy cell line Ref showed a growth rate of (25-63) %, as shown in Table (3), and Fig. (9) represents the relationship of the biological activity of cell growth between cancer cells and healthy cells. These results indicate the possibility of using low concentrations as an antidote for breast cancer, as it is considered effective on cancer cells and has little toxicity on normal cells, and Figure (11 and 10) shows the effect of the compound MA5 on healthy and cancerous cells.…”
Section: Vitality Assessment Of Compound Ma5mentioning
confidence: 96%
“…It had prepared by the condensation of Schiff bases with carboxylic acid anhydride (3,4). Their chemical structure has a distinctive feature in pharmacological chemotherapy drugs: antimicrobial (5), anti-cancer and anti-tuberculosis (6,7), anti-inflammatory (8), antioxidant (9), antifungal (10), and antibacterial. As auxiliary agents and in the manufacture of dyes as coloring materials, inhibitors of metal corrosion (11), and has a varied biological activity, its effectiveness used as an anticoagulant (12), treatment of mental disorders (13,14), anti-tumor (15), (16).…”
Section: Introductionmentioning
confidence: 99%